Applying the Policy Ecology Framework to Philadelphia’s Behavioral Health Transformation Efforts - Powell, Byron J. (Adm Policy Ment Health, 2016)
Raghavan et al. (2008) proposed that effective implementation of evidence-based practices requires implementation strategies deployed at multiple levels of the “policy ecology,” including the organizational, regulatory or purchaser agency, political, and social levels. However, much of implementation research and practice targets providers without accounting for contextual factors that may influence provider behavior. This paper examines Philadelphia’s efforts to work toward an evidence-based and recovery-oriented behavioral health system, and uses the policy ecology framework to illustrate how multifaceted, multilevel implementation strategies can facilitate the widespread implementation of evidence-based practices. Ongoing challenges and implications for research and practice are discussed.